2012
DOI: 10.1068/a44494
|View full text |Cite
|
Sign up to set email alerts
|

Rhythms of the Night: Spatiotemporal Inequalities in the Nighttime Economy

Abstract: The authors seek to extend the literature on inequalities and exclusion in the nighttime economy through a rhythmic analysis of visitor presence in public space in nightlife districts in the city centres of the Dutch cities of Groningen, Utrecht, and Rotterdam. Substantial inequalities in visitor presence, based on race/ethnicity and gender, are demonstrated. In the cities considered, racial/ethnic inequalities vary more in spatial terms, and gender inequalities fluctuate more heavily over the course of the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 27 publications
0
94
1
4
Order By: Relevance
“…Such work has offered important insights. For instance, Schwanen, Van Aalst, Brands, and Timan (2012) discuss the inability of some to participate as consumers in the night-time economy. The authors argue that, within the night-time economy, young people dominate, and there are also inequalities rooted in class, race/ethnicity and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Such work has offered important insights. For instance, Schwanen, Van Aalst, Brands, and Timan (2012) discuss the inability of some to participate as consumers in the night-time economy. The authors argue that, within the night-time economy, young people dominate, and there are also inequalities rooted in class, race/ethnicity and gender.…”
Section: Introductionmentioning
confidence: 99%
“…According to the city's website, almost half of the population of 16 years and older is highly educated (at least a bachelor degree or equivalent) and 22 per cent of the city's inhabitants are of non-Western descent. 3 Our previous research has shown that the nightlife district in Utrecht is disproportionally White compared with the city's resident population (Schwanen et al, 2012): only 11 per cent of the consumers in the NTE were of non-White extraction. The Whiteness of Utrecht's NTE primarily reflects the supply of bars and clubs, which are oriented strongly towards highly educated (White) students and young urban professionals who live in/around the city.…”
Section: Towards the Empirical Analysismentioning
confidence: 99%
“…Three forms of ambiguity, defined as the absence of stable and welldetermined effects, can be identified (1 Our empirical analysis is situated in Utrecht-a historic city with a population of 6316,000 inhabitants, in The Netherlands. Nightlife facilities are clustered in the city centre, consisting of a mix of restaurant, cinemas, (small) pubs and clubs without strict 'closing times' or regulation of alcohol sales (Schwanen et al, 2012). Utrecht was selected because it is the fifth-largest city in The Netherlands and one of the first to develop and implement Safe Nightlife Policies (van Liempt and van Aalst, 2012).…”
Section: Towards the Empirical Analysismentioning
confidence: 99%
“…This sense of control written through control of schedules is one that echoes in Schwanen et al's (2012) paper. Here the patterning of nightlife is used to look at who regulates the temporalities of the nighttime economy.…”
mentioning
confidence: 99%